What Matters Most for Student Assessment Systems : A Framework Paper - Clarke, Marguerite (World Bank, Washington, DC, 2014)
The purpose of this paper is to provide an overview of what matters most for building a more effective student assessment system. The focus is on systems for assessing student learning and achievement at the primary and secondary levels. The paper extracts principles and guidelines from countries' experiences, professional testing standards, and the current research base. The goal is to provide national policy makers, education ministry officials, development organization staff, and other stakeholders with a framework and key indicators for diagnosis, discussion, and consensus building around how to construct a sound and sustainable student assessment system that will support improved education quality and learning for all.